(untitled) (Fiep Bulletin - online, 2014)
The mechanical of the intervertebral discs have for objective dissipate loads and is related with the reduction and increase of stature from the individuals during the day. Some studies have demonstrated that overloads change the capacity of the intervertebral discs to dissipate loads. This study aim to compare the recuperation of stature among individuals obese and non-obese to identify if the fat engages this mechanic property of the intervertebral discs. For this, 20 male individuals, 10 obese (BMI>30) and 10 non-obese (BMI<25) had their stature variation verify after a daily task. There was a significant difference among the recuperation of stature of obese and non-obese individuals (obese: -0,066 mm /non-obese: 3,69 mm, p<0,001), where the obese participants recover less stature than the non-obese participants. The difficulty of recovering stature from the obese participants may be considerate a risk factor about the development of back pains and also may be considerate one of the explaining factors related to the higher incidence back pains in this individuals.